2017
DOI: 10.1097/md.0000000000007868
|View full text |Cite
|
Sign up to set email alerts
|

Composite hepatocellular carcinoma and small cell carcinoma with early nodal metastasis

Abstract: Rationale:Hepatocellular carcinoma (HCC) is known to grow in a mosaic pattern, and it can sometimes be combined with non-hepatocellular cells. Despites the variety of combination, HCC with a significant neuroendocrine carcinoma (NEC) component remains very rare. Most of the reported cases were treated as conventional HCC with a relatively poor prognosis. Early diagnosis may lead to a better treatment modality. Here, we report a case of composite HCC and small cell carcinoma (SCC) with nodal metastasis of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…They observed β-catenin staining in both components of the tumor and stated that these findings did not support exon 3 mutations in the CTNNB1 gene. In our case, similar to the case presented by Liu et al , 10 a strong β-catenin staining was observed in the HCC component. However, we did not observe β-catenin expression in the NEC component, leading us to speculate that in these tumors, divergent underlying molecular pathways might take place that involve the β-catenin pathway.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…They observed β-catenin staining in both components of the tumor and stated that these findings did not support exon 3 mutations in the CTNNB1 gene. In our case, similar to the case presented by Liu et al , 10 a strong β-catenin staining was observed in the HCC component. However, we did not observe β-catenin expression in the NEC component, leading us to speculate that in these tumors, divergent underlying molecular pathways might take place that involve the β-catenin pathway.…”
Section: Discussionsupporting
confidence: 91%
“…However, 3 of the 7 reported collision tumors of HCC-NEC were also detected in cirrhotic background. 6 , 10 , 20 These data support that HCC-NEC should be considered either clinically and pathologically in all patients with chronic liver diseases, regardless of the presence of cirrhosis.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations